Explanasi Kualitas Layanan Melalui Kompetensi Dinamis Untuk Meningkatkan Keputusan Pembelian Pada Ritel Skala Mikro - Feti Fatimah; Wenny Murtalining Tyas; Fahmy Muhammad Ulviano Putra (Jurnal Manajerial, 2026)
Background – Micro-scale retailers need innovative solutions to face competition from modern retailers. Explanations for improving retail service quality are necessary, as retaining existing customers is more efficient than acquiring new ones. Aim – Analyze the role of dynamic competency in mediating the relationship between service quality and purchasing decisions in micro-scale retail in developing countries. Design / methodology / approach – This study aims to analyze the role of dynamic competence as a mediator in the relationship between service quality and purchasing decisions in micro-scale retail in developing countries. The population of this study was micro-scale retail consumers in Jember Regency. The sample was drawn using probability sampling with a sample size of 600 respondents. Findings – Service quality has a positive and significant effect on dynamic competence. Service quality has a positive but insignificant effect on purchasing decisions. Dynamic competence has a positive and significant effect on purchasing decisions. Dynamic competence acts as an intervening factor in the relationship between service quality and purchasing decisions. Conclusion – Micro-scale retail must provide friendly and prompt service and ensure that this service translates into a tangible competitive advantage. Without increased competency, service quality alone is insufficient to significantly influence customer purchasing decisions Research implication – This research makes an important theoretical contribution to micro-scale retail, namely that service quality has a significant positive effect on dynamic competency. Practical implications for micro-scale retailers are that service quality plays a crucial role in building dynamic competency, such as the ability to understand customer needs, handle complaints, and customize services. Micro-scale retailers need innovative solutions to face competition from modern retailers. Dynamic competency can be an effective strategy for adapting and optimizing resources. Limitations – This analysis is limited to micro-scale retail in Jember district.